Looking back at prospective modeling of outbreak response strategies for managing global type 2 oral poliovirus vaccine (OPV2) cessation - Thompson, Kimberly M.; Kalkowska, Dominika A.; Badizadegan, Kamran (Frontiers in Public Health, 2023)
Ongoing detection of poliovirus transmission and use of oral poliovirus vaccine (OPV) continue to delay poliomyelitis eradication. In 2016, the Global Polio Eradication Initiative (GPEI) coordinated global cessation of type 2 OPV (OPV2) use for preventive immunization and limited OPV2 use to emergency outbreak response. In 2019, GPEI partners accelerated the development of a genetically modified novel OPV2 vaccine (nOPV2) that promised greater genetic stability, while preserving the mucosal immunological benefits induced by monovalent Sabin OPV2 (mOPV2). We reviewed integrated risk, economic, and global poliovirus transmission modeling performed before OPV2 cessation, which recommended multiple risk management strategies to increase the chances of successfully ending all transmission of type 2 live polioviruses. Following OPV2 cessation, strategies implemented by countries and GPEI deviated from model recommended risk management strategies. Complementing other modeling that explores prospective outbreak response options for improving outcomes for the current polio endgame trajectory, in this study we roll back the clock to 2017 and explore counterfactual trajectories that the polio endgame could have followed if GPEI had: (1) managed risks differently after OPV2 cessation and/or (2) developed nOPV2 before and used it exclusively for outbreak response after OPV2 cessation. The implementation of the 2016 model-based recommended outbreak response strategies could have and could still substantially improve the probability of ending type 2 poliovirus transmission. Outbreak response performance observed since 2016 would not have been expected to achieve OPV2 cessation with high confidence, even with the availability of nOPV2 prior to the 2016 OPV2 cessation. While nOPV2 offers benefits of lower risk of seeding additional outbreaks, the model results demonstrate how its reduced secondary spread relative to mOPV2 may imply relatively higher coverage needed for nOPV2 than mOPV2 to stop outbreaks.